Akselerasi Filantropi Islam di Timur Indonesia: Peran Literasi Zakat, Tingkat Pendapatan dan Adopsi Fintech Terhadap Keputusan Muzzaki Membayar Zakat di Kota Jayapura - Shimah Fauziah Yeubun (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
Eastern Indonesia harbors enormous yet underdeveloped potential for Islamic philanthropy, and Jayapura City as the economic epicenter of Papua offers a strategically significant context for understanding the dynamics behind muzakki's decision to fulfill their zakat obligations. This study aims to analyze the influence of zakat literacy, income level, and fintech adoption on muzakki's zakat payment decision in Jayapura City, both partially and simultaneously. Drawing on a sample of 210 muzakki selected through purposive sampling, data were collected using a structured Likert-scale questionnaire (1–5) comprising 26 indicators across four research constructs. Data analysis employed Partial Least Square- Structural Equation Modeling (PLS-SEM) via SmartPLS 3.0. Measurement model evaluation confirmed that all indicators met the required validity and reliability thresholds, with outer loadings ranging from 0.737 to 0.844, AVE from 0.622 to 0.691, and Composite Reliability from 0.899 to 0.938. The structural model yielded an R² of 0.855, indicating that the three predictors jointly explained 85.5% of the variance in zakat payment decisions. Bootstrapping results confirmed that Zakat Literacy (β = 0.597; T = 18.071; p = 0.000), Income Level (β = 0.567; T = 19.199; p = 0.000), and Fintech Adoption (β = 0.408; T = 12.482; p = 0.000) each exerted a positive and significant effect on muzakki's zakat payment decision. Zakat Literacy emerged as the most dominant predictor (f² = 2.451), followed by Income Level (f² = 2.208) and Fintech Adoption (f² = 1.144). These findings underscore the critical need for systematic zakat literacy programs, community economic empowerment, and accelerated digitalization of zakat services in Eastern Indonesia as evidence-based strategies for optimizing zakat collection in the region.